Reinterpretasi Hadis Tentang Gerakan Sujud - Apriliah, Apriliah; Takrip, Muhamad; Heriansyah, Dafis; Sarmilah, Sarmilah; Bahiroh, Bahiroh (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2023)
This study aims to discuss the reinterpretation of the hadith about the prostration movement. In this study, researchers do not need a place to research, but use a lot of literature research techniques. Data analysis technique used in this research is qualitative data analysis technique. The results and discussion in this researcher conclude that in the reinterpretation of the hadith about the prostration movement, there are two opinions, the first is the method of prostration, namely both knees first and then both hands. While the second opinion, namely the two hands first then the knees. This study concludes that when we prostrate we should not put our hands before our knees or vice versa. This means that there is no special way that we must do. According to the opinion of the narrator Abdul Aziz ibn Muhammad al-Darawardi. This study recommends religious and educational institutions to expand knowledge.